Asuhan Kebidanan Komprehensif Pada Ny. A G3P2A0 Umur 32 Tahun dengan Faktor Resiko Riwayat Caesar dan Anemia di Wilayah Kerja Puskesmas Paguyangan - Ulfi Laelatus Sa’diyah; Himatul Khoeroh; Widi Astuti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Serotinus is one of the obstetric complications that needs to be watched out for and there is a high risk of caesarean section during delivery. These complication will be made worse if the mother experiences anemia which can cause uterine atony, post partum bleeding and even lead to maternal death. According to WHO (2021), the Maternal Mortality Rate (MMR) is 329,000 per 100,000 live births, data from the Brebes Health Office in 2022 is 105 cases, and data from the Paguyangan Community Health Center (2021) is 4 cases. Researchers implemented comprehensive midwifery care using Varney and SOAP documentation. This research uses a qualitative descriptive method with a case study approach. Data collection used interview methods, observation, physical examination, supporting examinations, medical records, KIA books and other literature. The main informant is Mrs. A, while additional informants were midwives, general practitioners, obstetricians, nutrition officers, laboratory officers, husbands and families. Based on the results of pregnancy, childbirth, newborn, postpartum and family planning care, there were only problems in pregnancy at the age of 29+1, namely breech and oblique presentation and mild anemia with HB 9.6 g/dL and at the gestational age of 31+3, namely underestimation of fetal weight.